DWT based digital watermarking fidelity and robustness evaluation - Del Colle, Franco A. (2008)
An Image Adaptive Watermarking method based on the Discrete Wavelet Transform is presented in this paper. The robustness and fidelity of the proposed method are evaluated and the method is compared to state-of-the-art watermarking techniques available in the literature. For the evaluation of watermark transparency, an image fidelity factor based on a perceptual distortion metric is introduced. On the other hand, a degradation factor is introduced for the evaluation of watermark robustness against JPEG compression and resizing. The new fidelity metric allows a perceptually aware objective quantification of image fidelity. The suitability of the proposed metric for the fidelity evaluation of still image watermarking is supported by simulation results.